The impact of austerity on policy capacity in local government. (1st July 2019) - Eckersley, Peter; Tobin, Paul
Abstract : Scholars have found it difficult to identify the impact of austerity on policy outputs. This difficulty may have arisen because studies tend to focus on the content of national and EU legislation, or budgetary responses to fiscal constraint, rather than taking a holistic view of 'policy'. Drawing on fieldwork in two English cities, we show how 'dismantling by arena shifting' ‐ exemplified by reductions in 'back-office' environmental policy capacity at the subnational level ‐ can provide a more nuanced understanding of national‐local interaction and policy change. We propose that such approaches may be common, because they allow policymakers to protect electorally popular 'frontline' services and more visible aspects of public goods provision, thereby avoiding blame for potentially unpopular decisions. However, dismantling by arena-shifting may have significant impacts over the medium-term, because reductions in 'back-office' functions may make it more difficult for subnational actors to develop, implement and enforce effective policy in future.